NUCLEAR MEDICINE IN THE DIAGNOSIS OF HIP PROSTHESIS INFECTIONS: A SYSTEMATIC REVIEW OF THE FUNCTIONAL APPROACH - de Souza, Jurcilei Nunes Felix; Valácio, Camilla Cosenza; Mota, Luciene das Graças; Machado, Carla Jorge (Editora Impacto Científico, 2025)
Infections associated with hip prostheses represent one of the most challenging complications in orthopedics, requiring accurate and early diagnosis to ensure appropriate treatment and functional preservation. This study conducted a systematic literature review aimed at evaluating the available scientific evidence on the effectiveness of nuclear medicine methods in diagnosing these infections compared with conventional anatomical imaging. The search was carried out in the PubMed database in April 2025 using the descriptor “Nuclear medicine and arthroplasties.” Fifteen studies addressing the use of radiopharmaceuticals in hip prostheses were included. The results demonstrated that techniques such as technetium-99m (⁹⁹ᵐTc)-labeled leukocyte scintigraphy and ¹⁸F-FDG PET/CT show high sensitivity and specificity, allowing differentiation between active infection and aseptic inflammation. Furthermore, functional and metabolic imaging methods proved less susceptible to metallic artifacts compared to traditional anatomical modalities. It is concluded that nuclear medicine is an essential diagnostic tool for periprosthetic hip infections, contributing to safer and more accurate therapeutic decisions, although it still faces limitations related to technological availability and diagnostic protocol standardization. DOI: https://doi.org/10.56238/edimpacto2025.060-025